(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The paleoecological significance of the ostracod faunas from the middle Serravallian-basal Tortonian of the Tremiti islands is briefly discussed. The fauna is typical of the bathyal environment throughout the investigated interval. Compositional changes recorded in the assemblages, however, indicate that bottom water conditions varied. Within the middle Serravallian, ostracods point to the existence of a lower thermospheric environment with possible feeble psychrospheric influences. In the latest Serravallian-basal Tortonian, the start of a gradual shift towards upper thermospheric conditions is recognizable. The species Bradleya (?) saxolensis Russo, 1966 is herein redescribed and placed into the genus Agrenocythere Benson, 1972.